Fine-mapping an association of FSHR with preterm birth in a Finnish population. - Sung Chun; Jevon Plunkett; Kari Teramo; Louis J Muglia; Justin C Fay (PLoS ONE, 2013)
Preterm birth is a complex disorder defined by gestations of less than 37 weeks. While preterm birth is estimated to have a significant genetic component, relative few genes have been associated with preterm birth. Polymorphism in one such gene, follicle-stimulating hormone receptor (FSHR), has been associated with preterm birth in Finnish and African American mothers but not other populations. To refine the genetic association of FSHR with preterm birth we conducted a fine-mapping study at the FSHR locus in a Finnish cohort. We sequenced a total of 44 kb, including protein-coding and conserved non-coding regions, in 127 preterm and 135 term mothers. Overall, we identified 288 single nucleotide variants and 65 insertion/deletions of 1-2 bp across all subjects. While no common SNPs in protein-coding regions were associated with preterm birth, including one previously associated with timing of fertilization, multiple SNPs spanning the first and second intron showed the strongest associations. Analysis of the associated SNPs revealed that they form both a protective (OR = 0.50, 95% CI = 0.25-0.93) as well as a risk (OR = 1.89, 95% CI = 1.08-3.39) haplotype with independent effects. In these haplotypes, two SNPs, rs12052281 and rs72822025, were predicted to disrupt ZEB1 and ELF3 transcription factor binding sites, respectively. Our results show that multiple haplotypes at FSHR are associated with preterm birth and we discuss the frequency and structure of these haplotypes outside of the Finnish population as a potential explanation for the absence of FSHR associations in some populations.